2017
DOI: 10.1016/j.rmed.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of habitual waterpipe tobacco smoking on pulmonary function and exercise capacity in young healthy males: A pilot study

Abstract: Habitual waterpipe tobacco smoking in young seemingly healthy individuals is associated with a greater burden of respiratory symptoms and impaired exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 35 publications
1
52
1
6
Order By: Relevance
“…Although this parameter is nonspecific and highly variable with less clinical relevance compared to other parameters (except PEF), midflows are effort independent and very sensitive for early airway and lung parenchymal disease. In other studies, the midexpiratory flow rate was found to drop significantly shortly after smoking WP [ 10 ]. This could possibly be an early predictor of small airway obstruction, and the implication of serial spirometry testing could then predict progression to full COPD [ 9 ].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Although this parameter is nonspecific and highly variable with less clinical relevance compared to other parameters (except PEF), midflows are effort independent and very sensitive for early airway and lung parenchymal disease. In other studies, the midexpiratory flow rate was found to drop significantly shortly after smoking WP [ 10 ]. This could possibly be an early predictor of small airway obstruction, and the implication of serial spirometry testing could then predict progression to full COPD [ 9 ].…”
Section: Discussionmentioning
confidence: 85%
“…Many of them perceive it as a safer method of smoking. Because young WPS users are usually asymptomatic and do not seek medical care, few studies have addressed WPS effects on respiratory health in this population [ 8 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations